Modeling and Analysis of Gallium Oxide Vertical Transistors. (1st January 2019) - Kotecha, Ramchandra; Metzger, Wyatt; Mather, Barry; Narumanchi, Sreekant; Zakutayev, Andriy
Abstract : Gallium oxide (Ga2 O3 ) based semiconductor devices are expected to disrupt power electronic applications in the near future. Due to the wide bandgap of Ga2 O3, it should be possible to fabricate power devices with higher breakdown voltages and lower on-state resistances compared to incumbent Silicon (Si) and Silicon Carbide (SiC) technologies. In particular, vertical metal-oxide field effect transistor (MOSFETs) and vertical Fin Field Effect Transistor (FinFETs) devices based on Ga2 O3  have been recently reported. Here, we present a comparative modelling study of such vertical Ga2 O3 power transistors using use Technology Computer Aided Design (TCAD) and analyze their electro-thermal performance under static and dynamic operating conditions. We find that the MOSFETs show a trade-off between the current gains and threshold voltages, as a function of device geometry and acceptor concentrations in the body region. In contrast, in the FinFETs structures it is possible to achieve normally-off operation by proper design of the fin width and its donor concentration, without p-type doping. Overall, the modeling and analysis results presented here can be used as a guide for experimental improvement of the vertical Ga2 O3 device performance for future power electronic applications.